Anomalia em genitália de um exemplar de fêmea de Lutzomyia intermedia Lutz & Neiva, 1912 (Diptera, Psychodidae). Nota Científica - Taniguchi, Helena Hilomi; Novelli, Miriam Almeida; Tolezano, José Eduardo (Revista do Instituto Adolfo Lutz, 1992)
Resumo indisponível